PENERAPAN METODE BESARAN PIVOT DALAM PENURUNAN RUMUS TAKSIRAN INTERVAL DARI KOEFISIEN REGRESI LINEAR SEDERHANA - Narr Herrhyanto (IKIP Siliwangi and I-MES, 2012)
Regression is the relationship between the independent variables X and Y response variables were expressed in a mathematical equation. Equations TSB will then constitute a regression equation. The linear regression equation is actually shaped Y = Î± + Î²X + Îµ. From the regression coefficients Î± and Î², then Î² is the regression coefficient changes affecting the response variable Y.Because the value of Î² is usually not known, then the value will be estimated based on sample data. In this case, Î² assessment which will be discussed in this paper is the estimation interval. In other words, how to shape the interval estimate formula of this Î². Thus, in this paper will explain how the derivation interval estimates of Î². In mathematical statistics there is a method used in the valuation of this interval, ie the amount of pivot method.